Complication after the reconstruction of the old patellar tendon rupture - Ninković, Srdjan; Golijanin, Petar; Milankov, Vukadin (Vojnosanitetski pregled, 2022)
Introduction. Chronic patellar tendon rupture (PTR) occurs rarely; its frequency and prevalence are unknown. There are very little data on the late patellar tendon reconstruction in rheumatoid arthritis and its complications. Case report. We presented a surgical repair of a PTR with early postoperative rupture of the contralateral patellar tendon for a 21-year-old woman with a past medical history of juvenile rheumatoid arthritis (treated with corticosteroids) who sustained initial injury 11 months prior to the presentation. The contralateral side was used for autograft harvesting. We used bone-tendon-bone (BTB) autograft and allografts followed by double-wire loop reinforcement and immediate postoperative mobilization. The patient was followed for 2 years, and the function of both knees was restored completely, with a full active range of motion. In this case, reconstruction of an 11-month-old chronic PTR (with complete resorption of the tendon and completely separated infrapatellar pads, complicated by the contralateral PTR) with BTB autograft and allografts and double wire loop reinforcement gave an excellent functional result. Two years after the surgical treatment, the extensor function of both knees was completely restored with a full range of movements. The patient reported satisfying outcomes and was able to return to all pre-injury activities without the assistance of orthopedic devices. Conclusion. This case report highlights the importance of the early diagnosis and describes operative techniques used in chronic PTR repair and treatments of the early postoperative complications such as rupture of the contralateral tendon.
Keywords: early diagnosis; orthopedic procedures; patellar ligament; postoperative complications; reconstructive surgical procedures; rupture